The multifaceted implications of mental fatigue on women's football players' performance in small-sided games - Donnan, K. J.; Bargh, M. J.; Swettenham, L.; Olthof, S.; Whitehead, A. (Psychology of Sport and Exercise, 2026)
Research shows that mental fatigue (MF) can negatively impact physical performance. However, the effects of MF during football match-play are not well understood, particularly in women, and its impact on psychological factors is less known (e.g., attentional focus). This study explored the physical and psychological effects of MF in women's football during 7 vs. 7 small-sided games (SSGs). 14 Women's National League players (M age = 25.9 ± 5.9 years) participated. A counterbalanced cross-over design was implemented involving a MF (30-min social media use), and a control condition (30-min sitting with teammates with no phone access) prior to 3 × 7-min SSGs, interspersed with 2-min rest. GPS was used to monitor work output. Participants had microphones attached and were asked to `think aloud` (TA) during SSGs; content analysis was used to examine players' attentional focus and communication. MF (visual analogue scale) and fatigue (BRUMS) increased pre-to post-MF (+1.95 ± 1.45, p < .001; +2.57 ± 3.33, p = .038) but in control (p = 1.00), and happiness (BRUMS) was lower in MF vs. control (-1.96 ±0 .68, p = .013). No differences were found between conditions for work output or RPE (ps > 0.05). Total TA was lower (p = .046) and there was less positive performance-related TA (p = .022) in MF (22.53 ± 13.11; 0.15 ± 0.38) vs. control (30.00 ± 17.84; 1.54 ± 2.11). There was more negative non-performance related communication (p = .031), and less joking with teammates (p = .020) with MF (0.85 ± 1.07; 1.69 ± 1.80) vs. control (0.08 ± 0.28; 4.39 ± 3.78). In sum, 30-min social media use was associated with reduced happiness, vigour and heightened perceptions of fatigue, and effected how able participants were to engage in TA, how positive their thoughts were, and how they communicated with teammates. Avoiding phone use prior to training and match-play may be worth considering. Further team-sport research could incorporate TA methods which the present study showed to be feasible, to understand more on players' cognitive processing in match-play.